Wave elevation between elliptical structures - Chatjigeorgiou, IK; Mavrakos, SA (2009)
The hydrodynamic interaction of waves with arrays of vertical elliptical cylinders is considered. The present paper aims at developing of an efficient calculation method for predicting the extreme elevation of the free surface, in the fluid domain between ship-shaped structures in close proximity. Linear potential theory is employed and the solution method is based on the semi-analytical formulation of the various velocity potentials in elliptical coordinates, using series expansions of Mathieu functions and the so-called addition theorem for Mathieu functions. Copyright © 2009 by ASME.